Implementasi KKN Universitas Pertiba dalam pengembangan UMKM Desa Tiram Kabupaten Bangka Selatan Melalui inovasi Branding dengan Pembuatan logo - Juhari Juhari; Arifin Faqih Gunawan; Alifah Oktavirgianti; Dicky Wahyudi; Deffy Angraini; Deli Deli (Jurnal Medika: Medika, 2025)
The Community Service Program (Kuliah Kerja Nyata/KKN) is a form of student dedication to society, aiming to provide real contributions to village development. One of these contributions is supporting Micro, Small, and Medium Enterprises (MSMEs) in Tiram Village, Bangka Selatan Regency. The main problem faced by local MSMEs is the lack of visual identity and branding, which makes it difficult for their products to be recognized and compete in the market. Through the KKN program of Pertiba University, students conducted data collection, interviews, and logo creation tailored to the characteristics of each business owner. The methods applied included field observation, participatory discussion, and need-based logo design. The results show that MSME owners benefited from the creation of business logos, as it enhanced product image, built consumer trust, and opened opportunities for digital marketing. This study confirms that student involvement through the KKN program has a positive impact on MSME development in rural areas, particularly in branding and strengthening the competitiveness of local products.